Faktor-Faktor yang Mempengaruhi Audit Delay pada Perusahaan Perbankan Swasta Nasional yang Terdaftar di Bursa Efek Indonesia - Thalitha Nesya Devina; Anik Yuliati (IPM2KPE, 2023)
This study aims to examine and determine the effect of profitability, company size, and auditor reputation on audit delay. The research method used in this study uses quantitative methods with research objects of national private banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2019 – 2021. The results of the simultaneous test of this study indicate that profitability, company size, and auditor reputation have an influence together against audit delay. The magnitude of the effect of profitability, company size, and auditor reputation on audit delay in national private banking companies is 42.5%. Based on the results of the partial test, it was found that profitability has a significant negative effect on audit delay, while company size and auditor reputation have no effect on audit delay. In conclusion, profitability contributes negatively to audit delay, while company size and auditor reputation do not contribute to audit delay. Keywords: Audit Delay, Profitability, Auditor Reputation, Company Size